Analysis of INIS, MSCI, INSPEC databases concerning the dynamics of publications on low-activated chromium alloys for use in the nuclear and fusion power engineering - Shepelev, A.G.; Kurilo, Yu.P.; Krivchenko, O.V.; Nemashkalo, O.N. (Вопросы атомной науки и техники, 2014)
The paper presents the results of scientometric analysis of data flows from the International Databases, over a period since 1971 to 2011, on low-activated chromium alloys suitable for operation under extremely hard conditions in nuclear and fusion reactors. A detailed analysis of three Databases makes it possible to obtain the data on temporal trends of publications and on contributions to them from different countries, as well as, to define the type of publications and their languages. It is shown that investigations and developments on low-activated chromium alloys are of current importance.